Strengthening the Values of Tolerance in the Concept of Religious Moderation Nasarudin Umar Perspective - Hamdani, Imron; Harto, Kasinyo; Yuniar, Yuniar; Munir, Munir; Ibrahim, Duski (JURNAL INDO-ISLAMIKA, 2023)
Indonesia stands as the world's most populous Muslim nation, holding a crucial position in the realm of Islamic moderation. The richness of diversity, encompassing religion, culture, language, and customs, serves as a potential catalyst for peace when approached with an attitude of mutual respect and appreciation for differences. However, in the absence of tolerance, the specter of intolerance emerges and paves the way for acts of violence. Recognizing this delicate balance, the pivotal role of religious leaders and scholars becomes evident. They play a crucial part in fostering an understanding of religious moderation. This understanding acts as a proactive safeguard, while thwarting the escalation of intolerance and violence. Employing a qualitative research method with a descriptive approach, this study focuses on Prof. Dr. K. H. Nasaruddin Umar, M.A., and Madrasah Tsanawiyah Istiqlal Jakarta. The data collection involved meticulous observation, thorough documentation, and insightful interviews. The findings underscore the significance of religious leaders in imparting insights on tolerance and the value of harmonious coexistence within religious communities. In the context of MTs Istiqlal Jakarta, the results illuminate the pivotal role of the clergy in nurturing an atmosphere of understanding. This is evident in the MCB program and congregational prayers, where students are actively engaged in learning to appreciate and respect one another, embracing the beauty of diversity. This study underscores the transformative impact of religious education in shaping attitudes and mitigating the seeds of intolerance and violence within society.